Evaluation of Microwave Ablation in 4T1 Breast Tumor by a Novel VEFGR2 Targeted Ultrasound Contrast Agents - Li, Xiaoyu; Xia, Shujun; Ji, Ri; Zhan, Weiwei; Zhou, Wei (Frontiers in Oncology, 2021)
Objectives A novel ultrasound contrast agent (UCA) VEGFR2-targeting iron-doped silica (SiO2) hollow nanoparticles (VEGFR2-PEG-HSNs-Fe NPs) was prepared and applied in microwave ablation for breast cancer to investigate its value in the evaluation of effectiveness after tumor ablation. Methods VEGFR2-PEG-HSNs-Fe NPs were prepared by using nano-SiO2, which was regarded as a substrate and etched by ferrous acetate, and then modified with anti-VEGFR2 antibody. Laser confocal microscope and flow cytometry were used to observe its main physicochemical properties, and biological safety was also investigated. After the xenograft tumor was treated with microwave ablation, the extent of perfusion defect was evaluated by ultrasound by injecting VEGFR2-PEG-HSNs-Fe NPs. Results The average particle size of VEGFR2-PEG-HSNs-Fe was 276.64 ± 30.31 nm, and the surface potential was −13.46 ± 2.83 mV. In vitro, the intensity of ultrasound signal increased with UCA concentration. Good biosafety was performed in in vivo and in vitro experiments. The enhanced ultrasound signal was detected in tumors after injection of VEGFR2-PEG-HSNs-Fe NPs, covering the whole tumor. The lesions, which were incompletely ablated, presented as contrast agent perfusion at the periphery of the tumor, and contrast enhanced ultrasound (CEUS) was performed again after complementary ablation. It was confirmed that all the lesions were completely ablated. Conclusion Nano-targeted UCAs VEGFR2-PEG-HSNs-Fe NPs had good biosafety and ability of specific imaging, which might be used as a contrast agent in CEUS to evaluate the efficacy of tumor ablation.